Strategies for Restoration of Soil Quality to Mitigate Land Degradation in Semi-Arid North Western Nigeria - Raji, B A (Annals of Arid Zone, 2019)
Soil degradation alone was reportedly estimated to affect approximately 485million Africans, with annual long-term costs of between US $ 95-279 billion. Increasingagricultural productivity in Nigeria, with its over 70% marginal/problem land and adecreasing per capital arable land (PCAL), would, therefore, need sound and adequateinformation on soil quality enhancement. Soil organic carbon (SOC) plays a crucial rolein influencing physical, chemical and biological properties, and the overall soil quality.Some common strategies for restoration of SOC include conservation tillage which reducesdecomposition, fallow, agroforestry, improved pasture and optimal fertilization whichimproves C levels through enhanced biomass production. After 6 years of natural fallow,the un-amended soils in the Samaru experiment recorded slight decrease in soil organicmatter (SOC) content from 7.04 t C ha-1 to 6.83 t C ha-1 representing about 3% reduction.This result shows that the resilient power of the un-amended soils (degraded) to selfrestorationis low under natural fallow. The potential for carbon sequestration by theuse of eucalyptus (Eucalyptus globulus) and neem (Azadirachta indica) trees in afforestationin NW Nigeria is about 23 g C m-2 yr-1 to 305 g C m-2 yr-1 over rates in unstabilizedsand dune (control). These values would increase substantially if management practicessuch as fertilization are introduced. The use of NPK between 1977 and 1995, a periodof 18 years in the Samaru experiment, improved SOC content from 4.95 t C ha-1 to 7.30t C ha-1, reflecting a rate of 13 g C m-2 yr-1. This rate is about 50% less the rate usingmanure alone and 75% less using manure with NPK. The use of N fertilization alonefor 18 years also resulted in an increase of about 2.83 t C ha-1 or 16 g C m-2 yr-1. In theNE Nigeria, the use of manure along with the selected restorative strategies gave thefastest options for restoring soil quality and productivity.Key words: Land degradation, soil organic matter, soil quality, biomass production.